Evaluation of application timing in fertilizer micro-dosing technology on millet production in Niger, West Africa - Hayashi, K; Abdoulaye, Tahirou; Gerard, Bruno G.; Bationo, B. André (Springer, 2008)
Micro-dosing technology has been developed by the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT) and its partners to help subsistence farmers in the Sahel improve inorganic fertilizer application. However, the ICRISAT's recommendations regarding fertilizer application through this technology are only applicable at sowing and do not allow any flexibility in terms of labor and/or capital management. In rural areas, fertilizer cannot always be applied at sowing due to financial and labor constraints. The purpose of this study was to evaluate the effect of the timing of fertilizer application on millet production. A 2-year on-station experiment and a 1-year on-farm field experiment were conducted in the western region of Niger, West Africa. Even under the heterogeneous climatic conditions of the region during our experimental period, the results showed that the trend was the same as observed in previous studies: millet production improved through fertilizer application compared to the control (without fertilizer). The harvest index was also higher compared to that of the control. This increased production was consistently the same for all application timings. The marginal value–cost ratio on the investment calculated using a budgeting analysis for the on-farm experiment showed that – regardless of application timing – millet farmers who fertilized their fields with inorganic fertilizer made more profit than those who did not (control). This was also true for farmers who were unable to fertilize at sowing – delayed application was still the more profitable option relative to the no fertilizer control. Our results indicate that small subsistence farmers can be offered more options for inorganic fertilizer application timing using the micro-dosing technology. Delayed inorganic fertilizer application can help small farmers who are often labor constrained at the sowing period improve their yields as well as their economic returns.